Phosphatases of α-synuclein, LRRK2, and tau: important players in the phosphorylation-dependent pathology of Parkinsonism - Taymans, Jean-Marc; Baekelandt, Veerle (Frontiers in Genetics, 2014)
An important challenge in the field of Parkinson’s disease is to develop disease modifying therapies capable of stalling or even halting disease progression. Coupled to this challenge is the need to identify disease biomarkers, in order to identify pre-symptomatic hallmarks of disease and monitor disease progression. The answer to these challenges lies in the elucidation of the molecular causes underlying PD, for which important leads are disease genes identified in studies investigating the underlying genetic causes of PD. Interestingly, evidence suggests that phosphorylation changes in 2 major dominant genes of PD, namely leucine-rich repeat kinase 2 (LRRK2) and α-synuclein (α-syn), are important in PD pathogenesis. LRRK2 and α-syn have been both linked to familial forms of PD as well as associated to sporadic PD. Another gene, microtubule associated protein tau (MAPT), has been genetically linked to a dominant form of frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) and genome-wide association studies report a strong association between MAPT and sporadic PD. Interestingly, LRRK2, α-syn and tau are all phosphorylated proteins, and their phosphorylation patterns are linked to disease. In this review, we provide an overview of the evidence linking LRRK2, α-syn and tau phosphorylation to PD pathology and focus on studies which have aimed at identifying phosphatases responsible for dephosphorylation of pathological phosphorylations. We also discuss how the LRRK2, α-syn and tau phosphatases may point to separate or cross-talking pathological pathways in PD. Finally, we will discuss how the study of phosphatases of dominant Parkinsonism proteins opens perspectives for targeting pathological phosphorylation events and may aid in identifying biomarkers to monitor early PD and PD progression.